Witchcraft and sumpah pocong: Transformation and resolution of cases with the issue of shamans in Banyuwangi - Kusairi, Latif (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
Many people believe that misfortunes such as illness, death, crop failure, livestock death, and divorce are caused by certain people with magical powers and knowledge called "witchcraft". Like many other areas in Indonesia, Banyuwangi is one of the areas stigmatized by a lot of witchcraft. This stigma is then embedded in society, something that is said to be rooted in myths from the past. Witchcraft which is attached to magical rituals is difficult to prove by state law, because the basis of proof is difficult. So we need another formula to solve this witchcraft case with other models. When the elements of culture and Islam came in, the way to solve witchcraft was done by involving these elements of culture and Islam. Ways such as the pocong oath and the oath of the Koran as a way to resolve the case. This tradition is then often carried out to resolve witchcraft cases in society as a substitute for positive law which is difficult to prove in this case.